2004
DOI: 10.1093/joc/54.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Modernization and Tradition in an Age of Globalization: Cultural Values in Chinese Television Commercials

Abstract: Abstract:Commercials (N = 496) shown on three Chinese TV stations in the summer of 2000 were analyzed to uncover the dominant value themes in the commercials. Thirteen value themes were identified as applicable in the current sample. This study found that the most dominant value themes emerged in the Chinese commercials were product effectiveness, family, modernity, beauty/youth, and pleasure indicating the prevalence of utilitarian values and the coexistence of both traditional and modern values in the world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…This was supported in a more recent study by La Ferle and Lee (2005) in a study of viewer attitudes toward advertising across South Korea, China, Taiwan, and the United States. It is interesting to note that, in particular, television advertising has been found to significantly aid in social development and supporting traditional values (Zhang and Harwood, 2004). This study showed that Chinese respondents had the most favorable attitudes towards advertising across all of the populations being studied.…”
Section: Rationale For Country Selectionmentioning
confidence: 73%
“…This was supported in a more recent study by La Ferle and Lee (2005) in a study of viewer attitudes toward advertising across South Korea, China, Taiwan, and the United States. It is interesting to note that, in particular, television advertising has been found to significantly aid in social development and supporting traditional values (Zhang and Harwood, 2004). This study showed that Chinese respondents had the most favorable attitudes towards advertising across all of the populations being studied.…”
Section: Rationale For Country Selectionmentioning
confidence: 73%
“…Consequently, the Chinese sample also indicated an increase in China's use of the individual/independence appeal between 1998 and 2014. This finding can be explained through the greater emphasis the Chinese society currently places on modern and constantly changing styles (Zhang & Harwood, 2004). Lin (2001) predicted that a younger millennial generation influenced by a search for a unique fashion could increase individual values.…”
Section: Discussionmentioning
confidence: 99%
“…Current research has recognized a change in Chinese commercials over time. Zhang and Harwood (2004) identified five dominant themes in Chinese commercials: product quality/effectiveness, family, modernity, beauty/ youth, and pleasure. They showed that the importance of family was still a leading traditional appeal (Zhang & Harwood, 2004).…”
Section: Cultural Values and Advertisingmentioning
confidence: 99%
“…Youth must gain employment to ensure care for parents (Shi, 2006). Employment values include self-discipline, persistence and performance of obligations (Zhang and Harwood, 2004). Chinese society views itself as a network of relationships, with politeness and loyalty the keys to success (Tsui and Windsor, 2001).…”
Section: Figure 1 the Attitude Systemmentioning
confidence: 99%